Microstructures and mechanical properties of double hot-extruded AZ80＋xSr wrought alloys - 关绍康 朱世杰 王利国 杨卿 曹文博 (Transactions of Nonferrous Metals Society of China, 2007)
The effects of Sr addition on microstructures and tensile properties of the as-cast and hot-extruded AZ80 alloys were studied by OM, SEM, EDS, XRD, DSC and Instron tester. The results show that the microstructures of as-cast alloys consist of a-Mg and β-Mg17Al12 phase. Sr gathers on the boundaries, and dissolves into β-Mg17Al12 phase or forms Mg17Sr2 phase. The grains of ascast alloys are refined and discontinuous net-shaped structure is formed. The compound phases on the boundaries become thicker with increasing Sr content. The ultimate tensile stress（UTS） and elongation are improved compared with the corresponding Sr-free alloy. After preliminary hot-extruding, the UTS is up to 308-320 MPa and elongation reaches 8.0%-13.5%. After double hot-extrusion, the dynamic recrystallization completes totally, and the UTS is up to 310-355 MPa, but the elongation does not change apparently. The alloy with 0.02%Sr （mass fraction） obtains the best comprehensive performance with the UTS of 355 MPa and elongation of 13.2%. The SEM morphology of fracture surface shows that the alloys with Sr present good ductility after double hot-extrusion.